Loss of MTAP expression is strongly linked to homozygous 9p21 deletion, unfavorable tumor phenotype, and noninflamed microenvironment in urothelial bladder cancer - Natalia Gorbokon; Niklas Wößner; Viktoria Ahlburg; Henning Plage; Sebastian Hofbauer; Kira Furlano; Sarah Weinberger; Paul Giacomo Bruch; Simon Schallenberg; Florian Roßner; Sefer Elezkurtaj; Maximilian Lennartz; et al. (The Journal of Pathology: Clinical Research)
Abstract Homozygous 9p21 deletions usually result in a complete loss of S‐methyl‐5′‐thioadenosine phosphorylase (MTAP) expression visualizable by immunohistochemistry (IHC). MTAP deficiency has been proposed as a marker for predicting targeted treatment response. A tissue microarray including 2,710 urothelial bladder carcinomas were analyzed for 9p21 deletion by fluorescence in situ hybridization and MTAP expression by IHC. Data were compared with data on tumor phenotype, patient survival, intratumoral lymphocyte subsets, and PD‐L1 expression. The 9p21 deletion rate increased from pTaG2 low (9.2% homozygous, 25.8% heterozygous) to pTaG2 high (32.6%, 20.9%; p < 0.0001) but was slightly lower in pTaG3 (16.7%, 16.7%) tumors. In pT2–4 carcinomas, 23.3% homozygous and 17.9% heterozygous deletions were found, and deletions were tied to advanced pT (p = 0.0014) and poor overall survival (p = 0.0461). Complete MTAP loss was seen in 98.4% of homozygous deleted while only 1.6% of MTAP negative tumors had retained 9p21 copies (p < 0.0001). MTAP loss was linked to advanced stage and poor overall survival in pT2–4 carcinomas (p < 0.05 each). The relationship between 9p21 deletions/MTAP loss and poor patient prognosis was independent of pT and pN (p < 0.05 each). The 9p21 deletions were associated with a noninflamed microenvironment (p < 0.05). Complete MTAP loss is strongly tied to homozygous 9p21 deletion, aggressive disease, and noninflamed microenvironment. Drugs targeting MTAP‐deficiency may be useful in urothelial bladder carcinoma. MTAP IHC is a near perfect surrogate for MTAP deficiency in this tumor type.